The Insertional History of an Active Family of L1 Retrotransposons in Humans - Boissinot, Stéphane; Entezam, Ali; Young, Lynn; Munson, Peter J.; Furano, Anthony V. (Genome Research, 2004)
As humans contain a currently active L1 (LINE-1) non-LTR retrotransposon family (Ta-1), the human genome database likely provides only a partial picture of Ta-1-generated diversity. We used a non-biased method to clone Ta-1 retrotransposon-containing loci from representatives of four ethnic populations. We obtained 277 distinct Ta-1 loci and identified an additional 67 loci in the human genome database. This collection represents ∼90% of the Ta-1 population in the individuals examined and is thus more representative of the insertional history of Ta-1 than the human genome database, which lacked ∼40% of our cloned Ta-1 elements. As both polymorphic and fixed Ta-1 elements are as abundant in the GC-poor genomic regions as in ancestral L1 elements, the enrichment of L1 elements in GC-poor areas is likely due to insertional bias rather than selection. Although the chromosomal distribution of Ta-1 inserts is generally a function of chromosomal length and gene density, chromosome 4 significantly deviates from this pattern and has been much more hospitable to Ta-1 insertions than any other chromosome. Also, the intra-chromosomal distribution of Ta-1 elements is not uniform. Ta-1 elements tend to cluster, and the maximal gaps between Ta-1 inserts are larger than would be expected from a model of uniform random insertion.